Evaluación de dos protocolos de desparasitación seriados contra endoparásitos gastrointestinales a equinos en la brigada de caballería blindada N° 11 Galápagos - Naranjo Aguilar, Carla Fernanda (2024)
In Ecuador, gastrointestinal parasitism in equines is a serious problem in horse production. The lack of knowledge about therapeutic alternatives has led to the excessive use of drugs, which affects the intestinal flora of horses and causes various symptoms. Furthermore, the abuse of these medications has generated resistance to treatments. In veterinary practice, deworming is a key strategy to control and reduce the parasitic load in equines. However, there are discrepancies regarding the effectiveness of the protocols and anthelmintics used, which has shown variability in the results of these procedures. The present research aimed to evaluate two serial deworming protocols against gastrointestinal endoparasites in equines, conducted at the 11th Galapagos Armored Cavalry Brigade in Riobamba. The serial deworming protocols compared were (1st, 2nd, and 3rd days) and (1st, 7th, and 15th days), using a combination of two anthelmintics (ivermectin and mebendazole). Each protocol included 26 horses, for a total of 52 experimental units. A descriptive statistical model and a normality test for the data were used. According to the results obtained, the protocol applied on days 1, 7, and 15 showed greater effectiveness in eliminating gastrointestinal parasites, with 78.95% of horses being free from infestations.